Tackling iatrogenic post-percutaneous access femoral artery pseudoaneurysm – a case series of multiple closure techniques - Halim Lim, Aidi Aswadi; Zakaria, Rozman; Yaacob, Yazmin (2023)
Femoral artery pseudoaneurysm is an important post-procedural complication following percutaneous access/intervention. Whilst it is uncommon, it causes significant anxiety among clinicians including interventionists as it exposes the clinician to litigation concerns.